SR123781A, a Synthetic Heparin Mimetic - Herbert, J. M.; Hérault, J. P.; Bernat, A.; Savi, P.; Schaeffer, P.; Driguez, P. A.; Duchaussoy, Ph.; Petitou, M. (Thrombosis and Haemostasis, 2001)
SR123781A, a synthetic hexadecasaccharide comprising an anti-thrombin (AT) binding domain, a thrombin binding domain, and a neutral methylated hexasaccharide sequence, was obtained from glucose through a convergent synthesis. SR123781A showed high affinity for human AT (Kd = 58 ± 22 nM) and was a potent catalyst of its inhibitory effect with regard to factor Xa (IC50 = 77 ± 5 ng/ml – 297 ± 13 U/mg) and thrombin (IC50 = 4.0 ± 0.5 ng/ml – 150 ± 30 U/mg). SR123781A which acted exclusively via AT (no effect via heparin cofactor II at a concentration of 6 g/ml) inhibited thrombin generation occurring via both the extrinsic and intrinsic pathways in vitro in human plasma. SR123781A did not compete for 3H-heparin binding to PF4 and did not activate platelets in the presence of plasma from patients with heparin-induced thrombocytopenia. After intravenous or subcutaneous administration to rats, rabbits or baboons, SR123781A displayed prolonged anti-factor Xa and anti-factor IIa activity ex vivo. After intravenous injection to baboons, decreases of the anti-factor Xa and anti-thrombin activities were parallel and disappeared with the same pharmacodynamics. Intravenous administrations of SR123781A strongly inhibited thrombus formation in an experimental model of thromboplastin-induced venous thrombosis in rats with an ED50 value of 18 ± 0.1 g/kg (vs 77 ± 3 g/kg for heparin). SR123781A inhibited arterial thrombus formation induced on a silk thread in an arterio-venous shunt and in the vena cava (ED50 values of 225 ± 10 and 27 ± 8 g/kg, respectively). Compared to standard and low molecular weight heparin and to presently used drugs, SR123781A exhibited a highly favourable anti-thrombotic/bleeding ratio therefore showing that it might be considered as a promising compound in the treatment and prevention of various thrombotic diseases.
Keywords: Heparin mimetic; SR123781A; Factor Xa; thrombin; thrombosis